The Influence of Sharia Financial Literacy, Technology, and Investment Knowledge on Investment Decisions Among the Millennial Generation - Nikmah, Isnadiatun; Mutia, Agustina; Putri, Nurrahma Sari; M. Nazori (International Journal of Islamic Finance, 2025)
Background: Investment refers to the act of allocating funds or capital into assets with the expectation of generating future profits. Sound investment decisions are typically grounded in meticulous financial planning and a comprehensive understanding of associated risks and potential returns. Objectives: This study aims to examine the influence of Islamic financial literacy, technology, and investment knowledge on investment decisions among the millennial generation in Jambi City. Novelty: In this study, investment decisions serve as the dependent variable, while Islamic financial literacy, technology, and investment knowledge are the independent variables. The research focuses on the millennial generation residing in Jambi City.Research Methodology / Design: This quantitative study employs a population of 151,855 millennial residents in Jambi City. A probability sampling technique was utilized to select 100 respondents. Data were collected through questionnaires using a Likert scale measurement. Analytical methods included validity and reliability tests, R-squared analysis, and hypothesis testing via bootstrapping using Smart PLS 4.0 software. Findings: The findings indicate that Sharia financial literacy exerts a positive yet statistically insignificant influence on investment decisions, whereas technology and investment knowledge demonstrate a positive and statistically significant impact on investment decisions. Implication: Future studies are encouraged to incorporate additional variables to identify other factors influencing investment decisions.